Money Politic Dalam Pemilihan Kepala Daerah Berbasis Pendekatan Hukum Progresif - Suparnyo, Suparnyo; Aji, Wahyu Jatmiko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The prohibition of giving money or other materials to influence voters in both the legislative and regional head elections, although in practice it is invisible and is no longer an open secret, but law enforcement feels very weak. Law enforcement is carried out on candidates for regional heads and representatives who are caught giving money or other materials known as money politics to win their partners in a transparent manner, let alone reaching the Court. So far, only certain individuals who happen to be caught giving money or distributing basic necessities from a candidate pair of regional heads to the community undergoing the legal process, while the intellectual actors have never been revealed, so Law Number 8 of 2015 is needed.